2017
DOI: 10.3892/etm.2017.4381
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study for the short-term effects of targeted high-intensity UVB and narrow-band UVB in the treatment of vitiligo

Abstract: Vitiligo is a common acquired depigmentation disorder for which many treatments have previously been used with varying effects. The aim of the present study was to evaluate the efficacy and safety of targeted high-intensity (TH) and narrow band (NB) ultraviolet B light (UVB) for vitiligo treatment. A total of 33 patients with vitiligo were enrolled in the present study. Patients with a symmetrical or near-symmetrical distribution of lesions on their bodies were selected for the present study. For each patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…e treatment of vitiligo is a long process and it is impossible to have only one treatment. erefore, the information of the vitiligo patient and the "prescription" that is the treatment plan or custom treatment plan must be preserved completely [9,10]. After each treatment is over, the next treatment can continue with the last treatment time, the number of treatments, and other data.…”
Section: (2) Analysis and Design Of Data Storage And Query Functionmentioning
confidence: 99%
“…e treatment of vitiligo is a long process and it is impossible to have only one treatment. erefore, the information of the vitiligo patient and the "prescription" that is the treatment plan or custom treatment plan must be preserved completely [9,10]. After each treatment is over, the next treatment can continue with the last treatment time, the number of treatments, and other data.…”
Section: (2) Analysis and Design Of Data Storage And Query Functionmentioning
confidence: 99%
“…Another study by Zhang et al. compared targeted high‐intensity UVB with NB‐UVB and found that targeted high‐intensity UVB was more effective overall but still did not produce significant improvement in acral lesions 24 . Similar poor response rates were observed in a study by Dong et al.…”
Section: Discussionmentioning
confidence: 58%
“…4 Another study by Zhang et al compared targeted high-intensity UVB with NB-UVB and found that targeted high-intensity UVB was more effective overall but still did not produce significant improvement in acral lesions. 24 The paucity of dermal stem cells at acral sites can be suggested as a potential factor contributing to the absence of pigmentation in these areas. 27 Failure of migration of melanocytes along outer root sheath to epidermis and scarcity of pilo-sebaceous units in hands and feet can also play a role in treatment resistance of acral vitiligo.…”
Section: Discussionmentioning
confidence: 99%